Kontribusi Perempuan dalam Menjaga Kelestarian Taman Nasional Kerinci Seblat - Andika, Eva Juniar; Anwar, Guswarni; Hendrastiti, Titiek Kartika (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Andika, E.J., Anwar, G., & Hendrastiti, T.K. (2023). Woman’s contribution in Preserving Kerinci Seblat National Park. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 498-506). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).In the implementation of forest area protection, women face obstacles to actively contribute because the obstacles for women in carrying out conservation activities were greater than the opportunities available, so women's participation was quite low. This study aimed to determine the category of women's contribution in protecting the Kerinci Seblat National Park area. Respondents were selected based on purposive sampling method. The types of women's activities were categorized as active, passive, and negative. The results of in-depth interviews showed that the highest percentage of respondents' job characteristics were farmers. The results of in-depth interviews showed that women have high motivation to participate in programs implemented by the Kerinci Seblat National Park management such as counseling, planting, and other programs that can contribute to preserving the Kerinci Seblat National Park. The active participation of women through tree planting activities in the Kerinci Seblat National Park area such as pine, candlenut, and other woody plants carried out on formerly encroached land. The results of in-depth interviews with respondents also showed other activities carried out by women in the Kerinci Seblat National Park area, namely the maintenance of candlenut plants until they become saplings. The average respondent's garden visited directly to the field contained forestry plants such as sengon, acacia, onion wood, and other trees. So, the women of Pal VIII Village had made an active contribution in preserving the Kerinci Seblat National Park area.